APLIKASI KAPUR CANGKANG KERANG DARAH (Anadara granosa) DENGAN DOSIS BERBEDA PADA TANAH GAMBUT UNTUK BUDIDAYA IKAN PATIN (Pangasius sp.) - Marsi, Marsi; Jubaedah, Dade; Wijayanti, Marini; Maswala, Depi (JARI : Jurnal Akuakultur Rawa Indonesia, 2025)
The application of lime is attempt to increase the pH of the soil and pond water for catfish culture in swamps which generally have low pH. Liming is not only affected by soil and water pH, but also the content of soil organic carbon. The purpose of this study was to determine the dose of blood cockle shell lime on the bottom soil of the pond in increasing the pH of the water culture medium as well as the survival and growth of catfish. This study used a completely randomized design (CRD) with 6 treatments and 3 replications.The treatments given were differences in the dosage of cockle shells lime, consisting of 6,000 kg ha-1 equivalent to CaO (P1), 8,000 kg ha-1 equivalent to CaO (P2), 10,000 kg ha-1 equivalent to CaO (P3), 12,000 kg ha-1 equivalent to CaO (P4), 14,000 kg ha1 equivalent to CaO (P5), and 16,000 kg ha-1 equivalent to CaO (P6). The results of this study indicate that P6 with a dose of 16, 000 kg ha-1 equivalent to CaO increased the initial soil pH from 3.2 to 7.8. As for water pH, the best dose is P3 treatment with a dose of 10,000 kg ha-1 equivalent to CaO which increases the initial pH from 3.40 to 6.97 and produces 100% survival of catfish, an absolute length of growth 5.52 cm and absolute of weight growth 11.15 g with feed efficiency of 97.14%.